How to Encourage Enterprise Formalization : Some Practical Hints for Policymakers in Africa - Kenyon, Thomas (Washington, DC : World Bank, 2022)
This policy note takes as its starting point the common view that there are benefits and costs to formal status and that formalization will occur only if entrepreneurs perceive it to be in their self-interest. No doubt part of the answer lies in reducing the costs and time required for compliance -- as the World Bank's Doing Business project has documented. But lowering barriers to entry is unlikely to be sufficient. Encouraging formalization requires us to understand the relationship between state and private business as a bargain. And it also challenges policy-makers and development practitioners to think not only about technical solutions but also about institutional mechanisms for improving relations between entrepreneurs and the state.